Compósitos poliméricos para imageamento óptico e por raios-x em tanques de simulação hidráulica - Reis, Maria Helena da Silva (2014)
This research is related to the investigation of new approaches for noninvasive imaging that allow registering the internal architecture of sedimentary deposits generated in hydraulic simulation tanks. The simulations are conducted to better understand the behavior of turbiditic currents, one of the principal process responsible for the deposition of sediments in deep oceanic waters. For this reason it is purpose of this work the preparation of polymer nanocomposite with inorganic filler for non-destructive testing, with properties and characteristics similar to Coal 205, material currently used in these simulations. The prepared composites presented specific weight and settling velocity speed values similar to Coal 205 and it was observed that the incorporation of the filler and the different dyes did not affected significantly the desired characteristics.